USING NET PRESENT VALUE METHOD IN ECONOMIC EFFICIENCY ANALYSIS FOR FOREST PLANTATION: PROBLEMS AND SOLUTIONS - Quang Ha, Nguyen (Journal of Forestry Science and Technology, 2024)
This paper discussed limitations in perception and application of Net Present Value (NPV) method in economic and financial analysis for forest plantation. Starting point of the discussion is a common fact in forest plantation that, while financial efficiency assessments based on NPV criterion of the forest plantation projects are satisfactory, most of the forestry state owned enterprises and other forestry units are facing huge financial difficulties. The author pointed out that, the reasons for that contradiction are significant errors in NPV method’s application. They are: Ad hoc selection of forest planting rotations; ignorance of risk premium; irrelevant treatment of inflation; and overuse of NPV per hectare. Consequently, NPV method has been failed to give a correct criterion for economic and financial assessment in forest plantation. Since the errors are right placed in teaching materials and legal documents, negative impacts caused by misusing of the method are long lasted and exaggerated. Based on the problems analysis, the author proposed the solutions for each issue: simultaneously solving problems of planted forest rotation period and NPV identification; including of risk premium in discount rate; consistently handling of inflation factor and price’s type in NPV calculation; and using of an appropriate set of criteria in economic and financial assessment. In the author point of view, the proposed solutions are rather simple and ready to use, the most concern is laid in a full awareness towards the existence of the problems and an immediate responses by people engaged in related academic and practical fields.